Mapeamento de habitats marinhos no banco dos Abrolhos - Secchin, Nelio Augusto (2011)
The continental shelf is composed of a tropical mosaic megahabitats that support a high diversity of habitats, and now have suffered from anthropogenic pressures. The development and application of geo-mapping studies of the marine substrate has provided increased knowledge of benthic habitats. The most important coral reef formation of the South Atlantic, Abrolhos Platform, does not have sufficient information to enable effective management. The present study aims at presenting a spatial distribution and characterization of the major fields of the Platform of the Abrolhos' megahabitats. To this end, we used data from direct and indirect geological research, with a combination of surveys covering methodological SSS, and echo sounder, ROV, and the basis for a hierarchical classification of megahabitats and integration with past data collected. Reaching an interpretative representation of the types of background of the region studied (50.500km²), the methodological application was able to generate a new vision for the Platform of the Abrolhos. We identified areas of reef megahabitat (17%), Rhodolite (51%) as well as the main features of each, with variations occurring in the distribution and occurrence in relation to the available bathymetric profile. A reef structures that occurs with the domain Rhodolite, the Buracas, is a particular habitat that may have a significant importance for the ecosystem of Abrolhos. The methodology was applied to generate a satisfactory representation of the distribution and description of marine megahabitats for the entire Abrolhos Platform. Thus offering a new approach to design studies of applied marine habitats along the Brazilian coast, is important for the space represented, contained in a unique region where there was a gap in knowledge about the distribution and characterization of this habitat throughout its length.